Optimalisasi Sumber Daya Manusia Kepolisian Republik Indonesia dalam Peningkatan Pelauanan Publik di Kepolisian Resor Gresik - Erieg Adi Cahyono* (Universitas Airlangga, 2017)
Police function in the state government system in the presence of police institutions is indispensable to the community. No community does not have a police institution. Police are tasked with maintaining the security and public Order (Kamtibmas). In addition, police also acted as law enforcement officers. Police are part of the criminal justice system along with other law enforcement officers, namely prosecutors and courts. The important role of human resources of Gresik in improving public services is very important to improve the quality that is in accordance with the expectations of the community and implemented in a unified network that is simple, open , smooth, precise, complete, reasonable, and affordable in accordance with the principles of public service.